“New vs. old Europe”: Contested hegemonies and the dual-guarantee strategy of the East European countries - Türkes Mustafa (Međunarodni Problemi)
The paper analyses the East European countries' (EEC) security strategy in light of contesting US and Franco-German hegemonic projects. The EEC' s quest for a dual-guarantee strategy, which aims to get hard security from the US through NATO and soft security from the EU, is detailed as to show objectives of the EEC. It is concluded that although this strategy may succeed in times of crisis, it is untenable in the long run because the terms of relations between the EEC and both the US and EU are largely defined by the latter two, not by the EEC. Thus, rather than escaping from one-way dependency, the EEC's dual-guarantee strategy may result in dual dependency on both the US and the EU.